Bridging the Orthodox/Behaviorist Divide. Issue 105 (17th January 2020) - Osband, Kent
Abstract : Capital markets are neither knowledge machines nor ships of fools. They are social learners, according to Kent Osband, continually correcting and refining their flawed predictions. Predictions are flawed because no one can sample the future. Instead, agents study the historical record, look for relevant trends, and project their continuation. Appreciating this can help transcend the false dichotomy between orthodox and behavioral finance.